The genus Gelsemium: An update - Dutt, V.; Thakur, S.; Dhar, V. J.; Sharma, A. (Pharmacognosy Reviews)
The review includes 103 references on the genus Gelsemium, and comprises ethnopharmacology, morphology, phytoconstituents, pharmacological reports, clinical studies and toxicology of the prominent species of Gelsemium. Alkaloids and iridoids constitute major classes of phytoconstituents of the genus. Most popular species of the genus are the Asian G. elegans and the two North American related species, G. sempervirens and G. rankinii. Gelsemium species are categorized under medicinal as well as poisonous plants. Amongst various species, G. elegans and G. sempervirens possess medicinal value, and have been traditionally used as nervous system relaxant. These plants have been explored exhaustively for their anticancer activity. In the concluding part, the future scope of Gelsemium species has been emphasized with a view to establish their multifarious biological activities and mode of actions.
Keywords: Alkaloids; anticancer; gelsemium; lridoids